2019
DOI: 10.1002/hpm.2934
|View full text |Cite
|
Sign up to set email alerts
|

Calling for confirmation, reassurance, and direction: Investigating patient compliance after accessing a telephone triage advice service

Abstract: Understanding the influence of a telephone triage advice service (TTAS) on patients seeking care is critical to realize enhancements in patient care, functioning of emergency departments (EDs), and effectiveness of the health system. This study addresses the question: what influence does a TTAS have on a patient's attendance at an ED and the wider health system? Records from 2016 to 2017 of 12,741 calls from a national TTAS were linked to 72,577 ED presentations to a hospital in regional Australia, retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Presenting symptoms with highest frequency among patients, included: abdominal or digestive problems, 6.8%–12.2% of calls 5 19 22 24 39 and respiratory problems, 11.3%–11.9% 39 24 of calls. The majority of calls were made by women (range: 59%–72%).…”
Section: Resultsmentioning
confidence: 99%
“…Presenting symptoms with highest frequency among patients, included: abdominal or digestive problems, 6.8%–12.2% of calls 5 19 22 24 39 and respiratory problems, 11.3%–11.9% 39 24 of calls. The majority of calls were made by women (range: 59%–72%).…”
Section: Resultsmentioning
confidence: 99%
“…Paediatric advice services provide guidance for parents, enhance clinician-patient communication, and improve parental satisfaction and accessibility to non-urgent health advice. [2][3][4] Given approximately one in five parents used the PAL, with a high proportion of parents calling multiple times, this highlights a demand for non-urgent medical advice during early childhood. While studies have shown a growing demand for medical triage and assessment hotlines, this has not been studied in a clinical trial setting.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with certain disadvantaging characteristics (e.g., female, > 65 or < 5 years, ethnic minority, migrant identity, and poverty) are often the most frequent users of TCs and other out-of-hours services. [9][10][11][12][13] Unsafe or ineffective TC services would aggravate the vulnerability of these patients and deteriorate their health status. Although many studies found TC services to be safe and effective, 3,10,14 concerns about the quality, safety, and impact of TCs persist.…”
Section: The Reviewmentioning
confidence: 99%